Determining temperature ratings for children's sleeping bags - Schlabach, Meredith; McCullough, Elizabeth A.; Eckels, Steven J. (My University, 2018)
Manufacturers label their sleeping bags with a temperature rating to assist consumers in selecting a bag that will provide them with an acceptable level of thermal protection under the expected conditions of use. These temperature ratings are typically based on thermal manikin testing and whole-body heat loss models. Due to physical and physiological differences between children and adults, existing adult sleeping bag temperature rating models cannot be applied to children's bags. Therefore, a model for determining the temperature ratings of children's sleeping bags is proposed. Issues related to measuring the thermal insulation of children's sleeping bags are also discussed. The results of the model indicate that an older child has a higher temperature rating than a younger child for the same level of insulation. This is due to the higher sleeping metabolic rate of younger children.
Citation: Schlabach, M., McCullough, E. A., & Eckels, S. J. (2018). Determining temperature ratings for children’s sleeping bags. International Journal of Industrial Ergonomics, 65, 153–160. https://doi.org/10.1016/j.ergon.2017.08.001
Keywords: Sleeping bag; Temperature rating; Insulation